English for a Global Future: Santri’s Perceptions and Aspirations toward English Mastery - Gufron Gufron; Syarifuddin Syarifuddin (Universitas Persada Indonesia YAI, 2025)
This study reports a community service program (Pengabdian kepada Masyarakat/PkM) aimed at exploring and strengthening santri’s perceptions and aspirations toward English mastery in an Islamic boarding school context. In the era of globalization, English proficiency is increasingly essential not only for academic and professional advancement but also for enabling santri to engage in global communication and represent Islamic values internationally. This program was conducted at Pondok Pesantren Salafiyah Syafiiyah Sukorejo and involved 100 santri as participants. A mixed-method approach was employed, combining a structured questionnaire and semi-structured interviews to obtain quantitative and qualitative data. The questionnaire measured santri’s attitudes toward English, motivation and passion for learning English, as well as perceived benefits and barriers, while interviews explored their experiences, challenges, and future aspirations. Quantitative data were analyzed descriptively using mean scores, standard deviations, and reliability coefficients, whereas qualitative data were analyzed thematically. The findings indicate that santri demonstrated highly positive attitudes and strong motivation toward English learning, particularly driven by aspirations for global engagement and the dissemination of Islamic values. However, moderate levels of confidence and limited practice opportunities were identified as key challenges. Overall, the program highlights the importance of communicative, supportive, and context-sensitive English learning initiatives in pesantren environments. The study recommends sustained English programs, increased speaking practice, and institutional support to enhance santri’s English proficiency in a sustainable manner.